Teaching classroom management – a potential public health intervention?. Issue 3 (1st June 2015) - Marlow, Ruth; Hansford, Lorraine; Edwards, Vanessa; Ukoumunne, Obioha C; Norman, Shelley; Ingarfield, Sara; Sharkey, Siobhan; Logan, Stuart; Ford, Tamsin
Abstract : Purpose: – The purpose of this paper is to explore the feasibility of a classroom management course as a public health intervention. Improved socio-emotional skills may boost children's developmental and academic trajectory, while the costs of behaviour problems are enormous for schools with considerable impact on others' well-being. Design/methodology/approach: – In total, 40 teachers attended the Incredible Years (IY) Teacher Classroom Management (TCM) intervention in groups of ten. Afterwards teachers attended focus groups and semi-structured interviews were completed with headteachers to explore whether TCM was feasible, relevant and useful, research processes were acceptable and if it influenced teachers' practice and pupils. Teachers completed standardised questionnaires about their professional self-efficacy, burnout and well-being before and after attendance. Findings: – In all, 37/40 teachers completed the course. Teachers valued sharing experiences, the support of colleagues in the group and time out to reflect on practice and rehearse new techniques. Most teachers reported that they applied the strategies with good effect in their classrooms. Teachers' questionnaires suggested an improvement in their self-efficacy in relation to classroom management ( p =0.03); other scales changed in the predicted direction but did not reach statistical significance. Research limitations/implications: – Although preliminary and small, these feasibility study findings suggest that it was worthwhile proceeding to a definitive randomised controlled trial (RCT). Practical implications: – Should the RCT demonstrate effectiveness, then the intervention is an obvious candidate for implementation as a whole school approach. Originality/value: – Successful intervention with one teacher potentially benefits every child that they subsequently teach and may increase the inclusion of socio-economically deprived children living in challenging circumstances in mainstream education.